Continuity, consolidation and change : towards a European era of vocational education and training - (:unkn) unknown (Office for Official Publications of the European Communities, 2009)
Cedefop has analysed the challenges and progress made in reforming VET systems in line with the mandate received in the Helsinki communiqué. On the eve of 2010, when the current Lisbon strategy will come to the end, this report also takes a brief look into the future. Cedefop's biennial reviews have monitored progress within the Copenhagen process. In line with the mandate received in the Maastricht and Helsinki communiqués 2004 and 2006, Cedefop presents this third review of progress in European VET. The report is based in particular on a survey of the Directors-General or Vocational Education and Training and country reports provided by Cedefop's network of reference and expertise (ReferNet). Some of the topics are Lifelong learning through VET, Improving quality of VET, implementing European tools. (BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; S 2.3 Berufsbildungspolitik; I 2.2 Europa; S 3.5.5.1 CEDEFOP; Europäischer Bildungsraum; EU-Bildungspolitik; Berufsbildungspolitik; Lebenslanges Lernen; Qualität; Europäischer Qualifikationsrahmen; Berufliche Weiterbildung